Behavioural plasticity in activity and sexual interactions in a social lizard at high environmental temperatures - Rossi, Nicola (2023)
Sexual selection often shapes social behavioural activities, such as movement in the environment to find possible partners, performance of displays to signal dominance and courtship behaviours. Such activities may be negatively influenced by increasing temperatures, especially in ectotherms, because individuals either have to withstand the unfavourable condition or are forced to allocate more time to thermoregulation by increasing shelter seeking behaviour. Thus, they “miss” opportunities for social and reproductive interactions. Moreover, behavioural displays of ectotherms closely depend on temperature; consequently, mate choice behaviours may be disrupted, ultimately modifying sexual selection patterns. Therefore, it would be interesting to elucidate how increasing temperatures associated with global warming may influence activity and social interactions in the species’ natural habitat and, specifically how high temperatures may modify intersexual interactions. Consequently, our aim was to explore differences in the daily pattern of social interactions in an ectotherm model, Tropidurus spinulosus, in two thermally different habitats and to determine how high temperatures modify mate choice. High environmental temperatures were found to be associated with a bimodal pattern in daily activity, which was closely linked to the daily variations in the thermal quality of the habitat; whereas the pattern and frequency of social displays showed less plasticity. The time allocated to mate choice generally decreased with increasing temperature since individuals increased the use of thermal refuges; this result supports the hypothesis of “missed opportunities”. Moreover, at high temperatures, both sexes showed changes in mate selection dynamics, with females possibly “rushing” mate choice and males showing an increase in intermale variability of reproductive displays. In our ectotherm model, plastic adjustments in the behavioural activity pattern induced by high temperatures, plus the modification of the displays during courtship may ultimately modify mate choice patterns and sexual selection dynamics.